Rare and new etiological agents revealed among 178 clinical Aspergillus strains obtained from Czech patients and characterized by molecular sequencing - Hubka, Vit; Kubatova, Alena; Mallatova, Nada; Sedlacek, Petr; Melichar, Jan; Skorepova, Magdalena; Mencl, Karel; Lyskova, Pavlina; Sramkova, Blanka; Chudickova, Milada; Hamal, Petr; Kolarik, Miroslav (Medical mycology, 2012)
A collection of 178 Aspergillus isolates, recovered from Czech patients, mostly from 2007-2011, was subjected to multilocus DNA sequence typing using the ITS region, β-tubulin, and calmodulin genes. An unusually wide spectrum of etiologic agents that included 36 species of Aspergillus is discussed in the context of recent taxonomic and clinical reports. Invasive aspergillosis (IA), onychomycosis, and otitis externa were the predominant clinical entities. Five cases due to species newly proven as etiologic agents of human mycoses, as well as cases with unique clinical manifestations caused by unusual agents are discussed in more detail. Three species (i.e., A. insulicola, A. westerdijkiae and A. tritici) were identified as the confirmed etiologic agents of non-dermatophytic onychomycosis. Emericella rugulosa was recovered from a premature newborn with a fatal necrotising disseminated infection and is reported for only the second time as the cause of IA. Furthermore, we document the first infection due to A. calidoustus in a patient with chronic granulomatous disease. The infection manifested as a latent brain aspergilloma with an unusual clinical-laboratory finding. In addition to the well-known agents of human mycosis, several rarely isolated or poorly documented species were identified. An undescribed cryptic species related to A. versicolor was found to be common among isolates linked to proven and probable onychomycosis. An isolate representing A. fresenii, or an unnamed sister species, were causal agents of otomycosis. Three well defined, and tentative new species belonging to section Cervini, Candidi and Aspergillus (Eurotium spp.), were associated with cases of probable onychomycosis.
Keywords: Emericella; geny hub; DNA, Fungal; Male; novorozenec nedonošený; Adolescent; Česká republika; Aspergillus; onychomykóza; Onychomycosis; Otitis Externa; Sequence Analysis, DNA; otitis externa; sekvenční analýza DNA; Aspergillosis; mužské pohlaví; aspergilóza; mladiství; DNA fungální; Czech Republic; novorozenec; Genes, Fungal; lidé; ženské pohlaví; Humans; mikrobiologické techniky; Infant, Newborn; Infant, Premature; tubulin; Microbiological Techniques; Female; lidé středního věku; Tubulin; Middle Aged